Cost-Efficient Hybrid WDM-MDM-Ro-FSO System for Broadband Services in Hospitals - Liang, Peidong; Zhang, Chentao; Nebhen, Jamel; Chaudhary, Sushank; Tang, Xuan (Frontiers in Physics, 2021)
The expansion of high-speed communication needs due to explosive growth of subscribers each year has led the researchers to design the next generation communication systems which can cope with the current growing demand. Millimeter waves, operated within the range of 30 GHz to 300 GHz, can become potential carrier for delivering large amount of data. However, in hospital scenarios, these radio waves are subjected to strict regulations due to direct impact on patients’ health as well as high interference with other medical devices which again imposes critical challenge on patients. Thus, it is a challenge for the researchers to provide communication/broadband services for transmission of such sensitive biomedical sensor data in hospitals locations. Radio over Free space (Ro-FSO) systems may become the attractive solution to deliver millimeter waves over free space link with high speed. Further, to expand the capacity of Ro-FSO systems, mode division multiplexing (MDM) plays a vital role in addition to wavelength division multiplexing (WDM) scheme. In this work, we have demonstrated the MDM-WDM scheme to deliver four channels with each one having the capacity of 10 Gbps up-converted to 40 GHz over FSO link which is suitable for providing broadband and communication services within the hospital premises. Moreover, the proposed WDM-MDM-Ro-FSO link is evaluated under different fog conditions.